Developmental Trajectories of Maladaptive Perfectionism Among African American Adolescents. Issue 5 (10th March 2013) - Herman, Keith C.; Wang, Kenneth; Trotter, Reid; Reinke, Wendy M.; Ialongo, Nicholas
Abstract : This study examined the developmental trajectories of maladaptive perfectionism over a 7‐year period among African American youth living in an urban setting ( N = 547). In particular, the study attempted to determine whether two maladaptive aspects of perfectionism (socially prescribed and self‐critical) changed over time and could be distinguished by variables in 6th and 12th grades ( M age at study entry [first grade] was 6.22 years [ SD = 0.34]). Four classes best described the developmental trajectories on both measures of maladaptive perfectionism: high, low, increasing, and decreasing. Sixth‐ and 12th‐grade correlates, including measures of internalizing symptoms, mostly confirmed the distinctiveness of these classes. Parallel process analyses suggested that the two processes are complementary, yet distinct. Implications regarding the prevention of maladaptive perfectionism are discussed.